Implementation of RSA And Base64 in Business Communication Benefits in Online Media - Rekno Sulanjari; Leonardo Budi Hasiholan; Firda Nisafera Ulfa; Rahma Jelita (Sean Institute, 2025)
The industrial era 4.00 has almost passed, replaced by the era 5.00 which forces micro, small and medium enterprises to be more innovative in collaborating their internal activities in order to develop their business towards a better direction, at least to survive. This is also the case at CV Candi Karya, where by negotiating the policies applied to its internal performance to its prospective consumers. The implementation of RSA and Base64 in the field of work that has been carried out so far is likely to be able to increase profits in business communication so that it is expected to be able to maximize the development of its business amidst the sluggish dynamics of economic turnover in the field of outdoor advertising. Based on the research above, it was also found that if the variables X1, X2 increase, then the variable Y also increases (positive correlation). And the level of RSA implementation and Base64 implementation in this study was 50.54%, while the remaining 49.46% was caused by other factors outside this study. Business communication in CV Candi Karya company is the most effective activity for the formation of organizational development compared to other activities, which can be monitored from discussion forums with clients or potential clients with a thit of 4.84. From the results of the study it can be concluded that the Implementation of RSA and Base64 has an effect on CV Candi Karya's business communication.